2017
DOI: 10.3390/molecules22030433
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Endotoxin Induces Late Preconditioning, Increases Peroxynitrite Formation, and Activates STAT3 in the Rat Heart

Abstract: Administration of low-dose endotoxin (lipopolysaccharide, LPS) 24 h before a lethal ischemia induces pharmacological late preconditioning. The exact mechanism of this phenomenon is not clear. Here we aimed to investigate whether low-dose LPS exerts late effects on peroxynitrite formation and activation of Akt, Erk, and STAT3 in the heart. Male Wistar rats were injected with LPS (S. typhimurium; 0.5 mg/kg i.p.) or saline. Twenty-four hours later, hearts were isolated, perfused for 10 min, and then used for bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Although enhanced peroxynitrite formation contributes to the pathophysiology of cardiovascular diseases, it was demonstrated that nanomolar concentrations of peroxynitrite inhibit leukocyte-endothelial cell interaction, which improves postischemic myocardial function [ 66 ]. Moreover, it was reported that peroxynitrite plays a role in triggering ischemic preconditioning and ischemic postconditioning [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although enhanced peroxynitrite formation contributes to the pathophysiology of cardiovascular diseases, it was demonstrated that nanomolar concentrations of peroxynitrite inhibit leukocyte-endothelial cell interaction, which improves postischemic myocardial function [ 66 ]. Moreover, it was reported that peroxynitrite plays a role in triggering ischemic preconditioning and ischemic postconditioning [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate gene expression changes at protein quantity and activity level, standard Western blot technique was used in case of phospho-AKT, AKT, phospho-FOXO3, and FOXO3 with GAPDH loading background at week 19 [Figure 1D; (38, 42, 43)]. Heart tissue samples ( n = 7–8) were homogenized with an ultrasonicator (UP100H Hielscher, Teltow, Germany) in RIPA (Radioimmunoassay) buffer (50 mM Tris–HCl (pH 8.0), 150 mM NaCl, 0.5% sodium deoxycholate, 5 mM EDTA, 0.1% SDS, 1% NP-40 (Cell Signaling, Carlsbad, CA, USA) supplemented with protease inhibitor cocktail and phosphatase inhibitors PMSF and NaF (Sigma, Saint Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In parallel to the upregulation of NOX enzymes LPS increased the expression of eNOS and phosphor eNOS, which was accompanied by increased NO generation. Previous studies have demonstrated that injection of LPS into rats increased cardiac levels of the peroxynitrite precursors NO and superoxide which reacted towards peroxynitrite 38 . Enhanced peroxynitrite formation was previously detected in granulocytes, monocytes, lymphocytes and plasma cells after challenge with LPS 39 .…”
Section: Discussionmentioning
confidence: 88%